A cost‐effectiveness analysis of robotic versus laparoscopic distal pancreatectomy. Issue 2 (11th February 2020) - Vicente, Emilio; Núñez‐Alfonsel, Javier; Ielpo, Benedetto; Ferri, Valentina; Caruso, Riccardo; Duran, Hipolito; Diaz, Eduardo; Malave, Luis; Fabra, Isabel; Pinna, Eva; Isernia, Roberta; Hidalgo, Alvaro; et al.
Abstract: Aim: There is no study in the literature that evaluates the cost‐effectiveness of robotic distal pancreatectomy (RDP) over laparoscopic distal pancreatectomy (LDP). We performed a comparative study of RDP and LDP with the aim of evaluating clinical and cost‐effective outcomes. Material and Methods: This is an observational, comparative prospective nonrandomized study. The primary end point was to compare the cost‐effectiveness differences between both groups. A willingness to pay of €20 000 and €30 000 per quality‐adjusted life year (QALY) was used as a threshold to recognize which treatment was most cost‐effective. Results: A total of 31 RDP and 28 LDP have been included. The overall mean total cost was similar in both groups (RDP: €9712.15 versus LDP: €9424.68; P > .5). Mean QALYs for RDP (0.652) was higher than that associated with LDP (0.59) ( P > .5). Conclusion: This study seems to provide data of cost‐effectiveness between RDP and LDP approaches, showing some benefits for RDP.